A taxonomic revision of the species of Licea subg. Licea (Myxomycetes) - Wrigley De Basanta, Diana; Mier, Carlos De; Lado, Carlos (Phytotaxa, 2023)
A taxonomic revision of the genus Licea, subgenus Licea, using type collections and SEM imaging of the type material is presented. The type specimens of 20 species were obtained and studied simultaneously, and detailed comparisons of morphological features by light microscope and SEM were made. In four other species only published information was analized. The SEM imaging of the type material has enabled clarification of some taxonomic characters, such as the number of peridial layers, ornamentation of the inner surface of the peridium, and the ornamentation of the epispore. As a result of this study a new species from Mexico, Licea ampullliformis, has been formally described, and synonymy has been found in the case of two species, L. castanea and the recently described L. bryocorticola. As no type material was found for L. minima, a neotype has been designated here. In the case of L. pusilla an epitype has been selected in addition to the illustration, published in 18th century, which was chosen as a lectotype. A dichotomous key of the species examined is proposed to facilitate their identification.